Pengembangan LKPD IPA Berbasis Discovery Learning Materi Pernapasan Manusia untuk Meningkatkan Keterampilan Proses Sains Siswa Kelas V Sekolah Dasar - Susila Ningsih, Neli; Widi Winarni, Endang; Juarsa, Osa (UNIB Press, 2025)
This study aims to develop Student Worksheets (LKPD) based on DL(DL) on the human respiratory system material to improve the science process skills of fifth grade elementary school students. The DLlearning model was chosen because it can help students find concepts independently through exploration and problem solving. This study uses the research and development (R&D) method with the ADDIE model consisting of five stages: Analysis, Design, Development, Implementation and Evaluation. The results of the study indicate that the Discovery Learning-based LKPD developed has a high level of validity based on the results of expert validation of material, language, and design. The product trial conducted at SD Negeri 6 Lubuklinggau and the effectiveness test at SD Negeri 1 Lubuklinggau showed that this LKPD can improve students' science process skills based on the recapitulation of the KPS component profile analysis, which includes the ability to observe with a conversion value of 99.5%, questioning and predicting with guidance of 91.8%, Planning and conducting independent investigations of 84.8%, Processing and analyzing data and information of 85.6%, Evaluating and reflecting of 90.0% and Communicating results of 81.8%. Responses from students and teachers also show that this LKPD is easy to use and interesting with a percentage of